Motivasi Belajar Matematis Siswa Melalui Model Pembelajaran Teams Games Tournament (TGT) - Nurullita Astriani; Muhammad Bayu Al Dhana (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
Motivation plays a crucial role in fostering students' enthusiasm for learning, thereby ensuring effective study activities and improved learning outcomes. In mathematics education, varied and innovative strategies are required to boost students' mathematical learning motivation, one such strategy is the Teams Games Tournament (TGT) learning model. This study aimed to analyze students' mathematical learning motivation using the TGT model. It employed a quasi-experimental research design and was conducted at SDN No. 053997 Sei Siur, Pangkalan Susu. The study population consisted of fourth-grade students, with class IV-A serving as the experimental group and class IV-B as the control group. Based on the results of t-test used in the research, that the t-count value > t-table namely 3,108 > 2,0067. The findings indicate that the mathematical learning motivation of students taught using the Teams Games Tournament (TGT) model was superior to that of students taught using conventional methods.